2019
DOI: 10.1097/pec.0000000000001816
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of Infants After a Brief Resolved Unexplained Event–Related Hospitalization

Abstract: Objective A brief resolved unexplained event (BRUE) in infancy is a common reason for visiting the emergency department. However, little is known about the long-term outcomes of such an event. This study evaluates future mortality, morbidity, and/or developmental outcome after a BRUE. Methods A single-center retrospective study performed in 2009 to 2013 included 87 hospitalized infants (<1 year old) fitting the American Academy of Pediatrics' criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…12 In another study in which researchers managed infants hospitalized with a BRUE for 5 years, excellent longterm prognosis was observed. 13 Our findings add to the evidence that most patients with a BRUE do not receive a serious explanatory diagnosis, despite high rates of diagnostic testing and consultation to identify a cause for the event.…”
Section: Figuresupporting
confidence: 54%
“…12 In another study in which researchers managed infants hospitalized with a BRUE for 5 years, excellent longterm prognosis was observed. 13 Our findings add to the evidence that most patients with a BRUE do not receive a serious explanatory diagnosis, despite high rates of diagnostic testing and consultation to identify a cause for the event.…”
Section: Figuresupporting
confidence: 54%
“…The latter is in line with the results of our study, since we showed that infants with BRUE have a good prognosis. Moreover, Ari et al [ 29 ] reported a retrospective study of 87 hospitalized infants younger than 1 year who experienced BRUE and concluded that infants hospitalized because of a BRUE seem to have a generally excellent prognosis. It seems that food thickeners treat visible regurgitation/vomiting in infants with GERD; however, their effect on overall GER episodes remains controversial [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…A single-center retrospective study of 87 inpatient children diagnosed with lower-risk BRUE in Israel revealed no deaths after 5 years of follow-up. 13 Of the 87 patients, global developmental delay, retarded speech development, and convulsions were observed in 1 (1.15%), 12 (13.7%), and 3 (3.45%) patients, respectively; however, the respective prevalence rates of these conditions were the same as those of the given age group. In another single-center retrospective study of 762 patients diagnosed with ALTE in the United States, adverse outcomes were defined as the presence of recurrence, aspiration, trauma, and death and were observed in 40 (9%) of 436 patients with ALTE-not-BRUE, 23 (9%) of 256 patients with higher-risk BRUE, and 2 (2.9%) of 70 patients with lower-risk BRUE.…”
Section: Discussionmentioning
confidence: 83%
“…In this study, although no adverse outcomes were observed in cases classified as lower-risk BRUE, there were only a few such cases. A single-center retrospective study of 87 inpatient children diagnosed with lower-risk BRUE in Israel revealed no deaths after 5 years of follow-up 13 . Of the 87 patients, global developmental delay, retarded speech development, and convulsions were observed in 1 (1.15%), 12 (13.7%), and 3 (3.45%) patients, respectively; however, the respective prevalence rates of these conditions were the same as those of the given age group.…”
Section: Discussionmentioning
confidence: 99%